2021
DOI: 10.3390/polym13213826
|View full text |Cite
|
Sign up to set email alerts
|

AC Electric-Field Assistant Architecting Ordered Network of Ni@PS Microspheres in Epoxy Resin to Enhance Conductivity

Abstract: By using the low loading of the conductor filler to achieve high conductivity is a challenge associated with electrically conductive adhesion. In this study, we show an assembling of nickel-coated polystyrene (Ni@PS) microspheres into 3-dimensional network within the epoxy resin with the assistance of an electric field. The morphology evolution of the microspheres was observed with optical microscopy and scanning electron microscopy (SEM). The response speed of Ni@PS microsphere to the electric field were inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Moreover, such alignment resulted in the percolation threshold concentration for the optimized electrical conductivity decreasing substantially from 10 to 2 vol%. Similarly, Chen et al [ 254 ] reported that nickel coated PS microspheres can be aligned in the epoxy matrix, resulting in the conductivity of aligned composites which was approximately three orders of magnitude higher than the unaligned composite (~10 −5 to ~10 −2 S/m) at a loading content of 15 wt%.…”
Section: External Fieldsmentioning
confidence: 91%
“…Moreover, such alignment resulted in the percolation threshold concentration for the optimized electrical conductivity decreasing substantially from 10 to 2 vol%. Similarly, Chen et al [ 254 ] reported that nickel coated PS microspheres can be aligned in the epoxy matrix, resulting in the conductivity of aligned composites which was approximately three orders of magnitude higher than the unaligned composite (~10 −5 to ~10 −2 S/m) at a loading content of 15 wt%.…”
Section: External Fieldsmentioning
confidence: 91%
“…The combination of micrometer-scale core and nanoparticle shell integrates the characteristics of both core and shell materials, thereby expanding the application range beyond that of single materials. Due to the unique features of functional composite microspheres, nanoparticle composite microspheres have found extensive use in energy storage, biomedicine, industrial catalysis, electronic technology, and other fields. …”
Section: Introductionmentioning
confidence: 99%
“…In an epoxide system case, crystal orientation was spontaneously changed by modifying the frequency below 10 Hz. The thermoset epoxy has the mobility to change its orientation until the structure is completely locked as a result of further gelation process and the direction of molecular orientation is influenced by its polarity, so the change of polymer structure can be achieved by modifying it in the presence of an electric field 40 …”
Section: Introductionmentioning
confidence: 99%
“…The thermoset epoxy has the mobility to change its orientation until the structure is completely locked as a result of further gelation process and the direction of molecular orientation is influenced by its polarity, so the change of polymer structure can be achieved by modifying it in the presence of an electric field. 40 Epoxy has found extensive use as a polymer matrix in composite applications. The properties of the cured resins are influenced by the specific conditions during the curing process.…”
mentioning
confidence: 99%